The Analysis of Students’ Learning Difficulties in Online Learning Activities during COVID-19 Pandemic - Samsul; Burhan, Kristian; Wati, Lesma; Wahyu (TOFEDU: The Future of Education Journal, 2022)
This study aims to describe of students’ difficulty in online learning during the Covid -19 pandemic. The research was conducted in SD KEMALA BHAYANGKARI 1 oadag utara by applying descriptive qualitative. Instrument of the research included questionnaire (Guttman scale) and interview. The respondents of the research consist of 9 students. The result of the research shows 1) the average of questionnaire was 68.83 (difficult category) and 2) based the interview, the difficulty in online learning during the Covid - 19 pandemic which included students did not have handphone, the internet network is not smooth, and internet quota was not adequate.